Refractive Index Dispersion of Organic–Inorganic Hybrid Halide Perovskite CH3NH3PbX3 (X═Cl, Br, I) Single Crystals. Issue 5 (25th March 2019) - He, Chongjun; Zha, Guoan; Deng, Chenguang; An, Yang; Mao, Rong; Liu, Youwen; Lu, Yuangang; Chen, Ziyun
Abstract: Optical dispersion properties are indispensable in the thorough design of modern perovskite‐based photonics devices. Based on inverse temperature crystallization (ITC) method, here, CH3 NH3 PbX3 (CH3 NH3 ═MA, X═Cl, Br, I) bulk single crystals are grown from precursor solution. X‐ray patterns indicate that the perovskite crystals have good crystallinity. MAPbCl3, MAPbBr3, and MAPbI3 crystals are transparent above 427, 574, and 823 nm, respectively. Refractive indices of MAPbX3 crystals are measured with different wavelength at 24 °C and reduced dramatically with the wavelength increase. Sellmeier dispersion equation fitted by least squares can be used to calculate the refractive index above the absorption edges. Refractive indices rank in the order of MAPbI3 > MAPbBr3 > MAPbCl3 at the same wavelength. The halogen elements have great influence on refractive indices. These results play a vital role in studying MAPbX3 nonlinear optical properties as well as in further designing photoelectric devices. Abstract : Refractive indices of CH3 NH3 PbX3 (X=Cl, Br, I) single crystals change with wavelength, and the halogen elements have a great influence on the refractive indices. Sellmeier dispersion equations are obtained and can be used to calculate the refractive indices in the low absorption region. These crystals have similar dispersion behaviors near the band gap, which depend on the characteristics of inter‐band transitions.